The Triumph and Fall of Socialist Accounting: a Historical Aspect - Mackevičius, Jonas (Ekonomika, 2005)
The object of the investigation is the socialist system of accounting, its achievements and downfall. The goal of the investigation was to investigate the spreading of the soviet system of accounting in the people’s democratic countries and the presumptions seeking to create the common unified system of socialist accounting. The paper describes the historical formation of socialist accounting principles; implementation of the soviet socialist accounting system in European people’s democratic countries; peculiarities and achievements of the national systems of financial accounting of the countries - members of the Council of Mutual Economic Assistance (CMEA); unification and integration of financial accounting in the countries-members of the CMEA; shortcomings of the socialist system of accounting, its fall and its role in the development of the world system of accounting. The methods of the investigation involved analysis and assessment of the scientific literature and of the legal acts regulating the management of accounting, as well as systematization and summarizing of the accumulated information.